SYNTHESIS OF 9-DECEN-1-OL - Jovic, Suncica; Stamenković, Lidija (Journal of process management and new technologies, 2018)
Considering that this paper deals with alcohols, we will point out their most important characteristics. We will follow the order known in the organic chemistry. Alcohols are divided into three large groups: - Primary alcohols, - Sterile alcohols, - Carbohydrates. Considering that we are interested in basic alcohols and the alcohols difficult to synthesize industrially, we will show simply and in the broadest terms some of the characteristics of all alcohols, as well as of unsaturated alcohols.